1998
DOI: 10.1097/00001756-199812010-00030
|View full text |Cite
|
Sign up to set email alerts
|

Parieto-occipital ∼1 0Hz activity reflects anticipatory state of visual attention mechanisms

Abstract: High-density eeg recordings revealed sensory specific modulation of anticipatory parieto-occipital approximately 10 Hz oscillatory activity when visually presented word cues instructed subjects in an intermodal selective attention paradigm. Cueing attention to the auditory features of imminent compound audio-visual stimuli resulted in significantly higher approximately 10 Hz amplitude in the period preceding onset of this stimulus than when attention was cued to the visual features. We propose that this pariet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

60
434
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 497 publications
(506 citation statements)
references
References 15 publications
60
434
0
Order By: Relevance
“…α-rhythms originating in the occipital region are associated with visual attention processes (e.g. Foxe et al, 1998) while α-rhythms generated by the sensorimotor cortex are related to motor processes (e.g. Hari et al, 1998).…”
Section: Eeg Data Acquisition and Preparationmentioning
confidence: 99%
“…α-rhythms originating in the occipital region are associated with visual attention processes (e.g. Foxe et al, 1998) while α-rhythms generated by the sensorimotor cortex are related to motor processes (e.g. Hari et al, 1998).…”
Section: Eeg Data Acquisition and Preparationmentioning
confidence: 99%
“…EROs in the alpha band (B10 Hz) were found to increase with memory load during the delay interval in a working memory task [9,13]. This increase in 10 Hz activity has been interpreted as a correlate of a cortical inhibition of taskirrelevant neural processes [14][15][16]. While most of these studies employed only single-featured objects, Klaver et al [11] used multi-featured objects to investigate the effect of feature-load on ERPs during encoding and retention and failed to find an effect of feature-load.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, α-activity might serve to shape the state of sensory brain regions to direct the flow of information and optimize performance (8). In support of this idea, several studies on visual perception have shown that anticipatory α-activity reflects the orienting of attention (9)(10)(11)(12)(13)(14) and influences detection performance (15)(16)(17). Recently, it was shown that the functionality of α-oscillations can be generalized to the somatosensory system (18)(19)(20)(21).…”
mentioning
confidence: 94%